DC Glow Discharge Plasma Characteristics in Ar/O2 Gas Mixture - Jabur, Younus K.; Hammed, Mohammed Gh.; Khalaf , Mohammed K. (Iraqi Journal of Science, 2021)
In this article, the effects of the O2 ratio on the electrical characteristics, including the I-V characteristic curve, Panchen’s curve, and I-P curve, were tested in a sample of O2/Ar gaseous mixture . The sample was produced by plasma-based DC magnetron sputtering with niobium metal as a target material. The inter-electrode spacing value was 4 cm. Plasma diagnosis via the Optical Emission Spectroscopy (OES) method was used to achieve Te and Ne mixture values of 20 %, 30 %, 50%, and 70% in the Ar/O2 system. The results showed that the discharge is operating in the abnormal glow region and the discharge current was decreased by increasing O2 percentage. In addition, the experimental results showed that the discharge is optimal at 30% gas ratio. It was found that the electron temperature was decreased with increasing working pressure and increased with increasing the O2 percentage, while electron density was increased with increasing both working gas pressure and O2 percentage.